Exchange rate bands of inaction and play-hysteresis in Greek exports to the euro area, the US and Turkey: Sectoral evidence - Ansgar Belke; Dominik Kronen (Research On Money in the Economy (ROME), 2015)
In this paper a non-linear model is applied, where suddenly strong spurts of exports occur when changes of the exchange rate go beyond a zone of inaction, which we call "play" area - analogous to mechanical play. We implement an algorithm describing path-dependent playhysteresis into a regression framework. The hysteretic impact of real exchange rates on Greek exports is estimated based on the period from 1995Q1 to 2014Q4. Looking at some of the main export partners of Greece, the euro area, Turkey and the US, and some of its most important tradeable sectors we identify significant hysteretic effects for a part of the Greek exports. We find that Greek export activity is characterized by "bands of inaction" with respect to changes in the real exchange rate and calculate the further real depreciation needed to trigger a spurt in Greek exports. To check for robustness we (a) estimate Greek export equations for a limited sample excluding the recent financial crisis, (b) use export weight instead of deflated nominal exports as the dependent variable, (c) employ a political uncertainty variable as a determinant of the width of the area of weak reaction. Overall, we find that those specifications which take uncertainty into account display the best goodness of fit. In other words: the option value of waiting dominates the real exchange rate effect on Greek exports.
Keywords: F14; C51; 330; real depreciation; Greece; play-hysteresis; modelling techniques; switching/spline regression; export demand